Effects of low-stearate palm oil and high-stearate lard high-fat diets on rat liver lipid metabolism and glucose tolerance. - Janssens, Sharon; Heemskerk, Mattijs M.; van den Berg, Sjoerd A.; van Riel, Natal A.; Nicolay, Klaas; van Dijk, Ko Willems; Prompers, Jeanine J. (Nutrition & Metabolism, 2015)
Background: Excess consumption of energy-dense, high-fat Western diets contributes to the development of obesity and obesity-related disorders, such as fatty liver disease. However, not only the quantity but also the composition of dietary fat may play a role in the development of liver steatosis. The aim of this study was to determine the effects of low-stearate palm oil and high-stearate lard high-fat diets on in vivo liver lipid metabolism. Methods: Wistar rats were fed with either normal chow (CON), a high-fat diet based on palm oil (HFP), or a high-fat diet based on lard (HFL). After 10 weeks of diet, magnetic resonance spectroscopy was applied for the in vivo determination of intrahepatocellular lipid content and the uptake and turnover of dietary fat after oral administration of 13C-labeled lipids. Derangements in liver lipid metabolism were further assessed by measuring hepatic very-low density lipoprotein (VLDL) secretion and ex vivo respiratory capacity of liver mitochondria using fat-derived substrates. In addition, whole-body and hepatic glucose tolerance were determined with an intraperitoneal glucose tolerance test. Results: Both high-fat diets induced liver lipid accumulation (p < 0.001), which was accompanied by a delayed uptake and/or slower turnover of dietary fat in the liver (p < 0.01), but without any change in VLDL secretion rates. Surprisingly, liver lipid content was higher in HFP than in HFL (p < 0.05), despite the increased fatty acid oxidative capacity in isolated liver mitochondria of HFP animals (p < 0.05). In contrast, while both high-fat diets induced whole-body glucose intolerance, only HFL impaired hepatic glucose tolerance. Conclusion: High-fat diets based on palm oil and lard similarly impair the handling of dietary lipids in the liver, but only the high-fat lard diet induces hepatic glucose intolerance.